PENGARUH AKUNTABILITAS, KOMPETENSI, PROFESIONALISME, INTEGRITAS, DAN OBJEKTIVITAS AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT DENGAN INDEPENDENSI SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA BEBERAPA KAP AFLIASI ASING DAN KAP NON AFLIASI ASING DI JAKARTA) - Trismayarni Elen; Sekar Mayang Sari (Media Riset Akuntansi, Auditing & Informasi, 2013)
This research was to obtain empirical evidence on the influence of Accountability, Competence, Professionalism, Integrity, and Objectivity of Public Accountant to the quality of audit with independence as Moderating Variable. The research was conducted by distributing questionnaires at several affiliated and non-affiliated registered public accountants located in Jakarta. Analysis modelused to test the hypotheses was multiple linear regression, these analysis was based on valid questionnaires from 117 respondents.These researchoutcomes concluded that the accountability and integrity of partially significant effect on the quality of audit, while the competence, professionalism, and objectivity had no effect on audit quality partially. In addition, this research proved that accountability moderated by theindependence significantly affected the quality of the audit, while the competence, professionalism, integrity and objectivity moderated byindependence had no significant effect on the quality of the audit.